Atención al cliente en la empresa Agrovent del Cantón Palenque durante el período 2023. - Velásquez Rendon, Nayely Nicolle (2024)
Customer service is a fundamental component for any company that seeks to maintain customer satisfaction and ensure customer loyalty. It is the process by which a company interacts with its customers to resolve their queries, complaints, and provide them with assistance in the purchase and use of products or services. This process encompasses a variety of communication channels, ranging from telephone and online service to in-person support in physical stores. Effective customer service is characterized by empathy, patience and the ability to solve problems efficiently. This involves not only addressing customer needs, but also anticipating their potential concerns and offering proactive solutions. In addition, it is important to maintain clear and transparent communication at all times, providing accurate and up-to-date information on products, company policies and any other aspect relevant to the customer. To provide quality service, companies often invest in the education and training of their customer service staff, ensuring that they are familiar with the products or services offered, as well as the company's policies and procedures. Additionally, many businesses use technology tools such as customer relationship management (CRM) systems to record and track customer interactions, allowing for more personalized and efficient service.